Anxiety and critical thinking in debate - Zulkifli Anthony, Norin Norain; Othman, Moomala; Ismail, Lilliati (Human Resource Management Academic Research Society, 2017)
Debate is often lauded as an excellent tool to encourage critical thinking skills and enhance speaking skills. However, some students claim that they feel apprehensive when taking part in this activity. Anxiety can be a motivating factor but for some it can be debilitating. This paper aims to measure the anxiety level of English as a Second Language (ESL) students at various points along the stages of undergoing a debate competition. It also aims to find out the anxiety level between male and female students and the anxiety level among students of three different critical thinking groups: low, moderate and high critical thinking ability. The findings show that students with low critical thinking ability experienced higher anxiety than those from the moderate or high critical thinking group. Findings also show that at the beginning of the competition, the female students were more anxious than the male students, but at the end of the competition the anxiety level tapered to almost the same level.